Pengaruh Suku Bunga Bank Indonesia dan Inflasi kepada Return On Aset (ROA) pada Bank Syariah di indonesia - Fikri, Ihsanul; Amri, Abrar; Mahdani, Rimal; Hastuti, Cut Sri Firman; Fatmayanti, Fatmayanti (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2025)
This study analyzes the impact of Bank Indonesia's interest rate and inflation on Return On Assets (ROA) at Islamic Banks in Indonesia from 2019 to 2023. Although Islamic Banks do not use an interest-based system, interest rates and inflation can still influence their performance, particularly in terms of financing and fund distribution. The research method employed is descriptive quantitative analysis with multiple linear regression. The results indicate that both interest rates and inflation, either individually or together, have a significant positive impact on the ROA of Islamic Banks.